Factores de riesgo y su influencia en la bronquitis aguda en niños menores de 5 años ciudadela gran Colombia Cantón Vinces - Los Ríos primer semestre 2018 - Morante Chanatasig, Danes Jair (2018)
The present investigation was developed in the Great Colombia Citadel of Vinces Province of Los Ríos, in the first semester of 2018, the same one that has as a general objective Identify the risk factors that influence acute bronchitis in children under 5 years Gran Colombia Citadel of the Vinces Canton, Province of Los Ríos, first semester 2018; the present topic seeks through bibliographic and field research, to find the mechanisms that help to reduce and if possible eradicate respiratory diseases, specifically acute bronchitis in children under five years of the aforementioned sector. This study has been carried out under a non-experimental methodology, that is, looking for the relationship between the variables without modifying the context of the same. The methods used were the inductive - deductive and analytical method, since it is based on the information obtained to perform the analysis of the problem under study. Also in the field research, structured surveys were conducted for parents of children under five years of age, which showed, among other things, the lack of knowledge on issues of prevention of acute bronchitis in their children, as well as also the risk factors in which they are immersed. Once the investigative process is finished, the need to plan training strategies on the prevention of respiratory diseases such as acute bronchitis is concluded.